Definition of morphological changes of hepar, myocardium and stomach cells in rats after carbamazepin and thyotriazolin administration - Opryshko V.I.; Skvyrska K.O.; Mamchur V.I.; Mazur I.A.; Kucherenko L.I. (Морфологія, 2012)
We investigated the histological changes in rats after new complex drug administration. Seventy male white rats were used for this experiment. During 90 days they received carbamazepin and thyotriazolin compound. Compound were administered orally via gavage. We observed damaging action of high dose carbamazepin on hepar, myocardium and stomach. Our data suggest that thyotriazolin reduce toxic effect of carbamazepin on hepar, myocardium and stomach.